2014
DOI: 10.1177/0044118x13513590
|View full text |Cite
|
Sign up to set email alerts
|

Understanding, Evidencing, and Promoting Adolescent Well-Being

Abstract: 23The wellbeing of young people is of considerable concern with many 24 initiatives targeting the health behaviors of this population. Educators are 25 amongst the professional groups being challenged to understand, evidence 26 and enhance childhood wellbeing. Working with a case study UK school 27 adolescent subjective wellbeing (SWB) was examined through the Introduction 42Wellbeing is referred to frequently within public policy and it has become a common 43 measure by which quality of life is judged (Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…,Kocayörük and Telef (2015),Lee (2016),Matthews et al (2015),Robertson (2013),and Stiglbauer et al (2013). The first part of the survey covered information regarding school location, school type, grade level, nationality, and gender.…”
mentioning
confidence: 99%
“…,Kocayörük and Telef (2015),Lee (2016),Matthews et al (2015),Robertson (2013),and Stiglbauer et al (2013). The first part of the survey covered information regarding school location, school type, grade level, nationality, and gender.…”
mentioning
confidence: 99%
“…Similar creative means of eliciting meaning have been used in previous wellbeing studies (Kostenius & Öhrling, 2006;Matthews et al, 2015). As a result of a pilot, the original drawing and collage plan was adapted into making a banner for the next cohort, advising them How to enjoy (and survive) the last year of primary school [in Slovak:…”
Section: Methodsmentioning
confidence: 99%
“…Parents talked about their children's worries about the 'bedroom tax', for example, about the potential need to move neighbourhoods or schools. Prior research has suggested that anxiety about the future is associated with lower levels of well-being in adolescents (Matthews et al, 2014).…”
Section: Impacts On Childrenmentioning
confidence: 97%